Indicators for sustainable development: understanding the criteria for a successful sustainability relevant to environmental law in Malaysia - Mustafa, Maizatun (Science Publishing Corporation Inc., 2018)
The concept of `sustainable development’ emerges in almost every discussion of environmental issues, be it at national or international levels. Over the years, especially after the famous 1987 Brundtland Commission’s Report, this concept has become more widely accepted by the policy-makers all over the world, including Malaysia. However, despite having received much international recognition and acceptance, the concept is still enigmatic and elusive, and there appears to be significant vagueness about exactly what meaning its exact denotation supposed to convey. This article seeks to examine the emergence and development of the concept of sustainable development at the international level, and to peruse its possible or suitable definitions. The objectives of such examination are to identify indicators that have greatly influenced the major discourse in the legal theories derived from this concept. For Malaysia and elsewhere, these sustainability indicators can be applied to appraise the effectiveness of legal mechanism in environmental protection and pollution control. The article concludes that understanding the criteria of successful sustainability allows a nation to meet the ongoing challenge of balancing present needs against those of the future. It is through this understanding that challenges and opportunities for sustainable development become clear.